Are South African public universities economically efficient? Reflection amidst higher education crisis - Marire, J. (South African Journal of Higher Education, 2017)
The question of free quality higher education has possessed the soul of the nation since the ‘fee-free university education for the poor report’ was withheld by the Minister of Higher Education and Training. The paper asks: are South African universities economically efficient and if they are efficient how many more students would they fully fund internally to increase financial access to, and academic success in, the academy? Using stochastic frontier modelling, I find that public universities, on average, are 12.7% cost inefficient. The deadweight loss is the equivalence of 79,231 potential undergraduates who were denied access to fully university-funded 3-year degrees between 2009 and 2013. Universities are ranked in terms of their inefficiency scores. Determinants of cost inefficiency are modelled and their implications discussed. The free quality education issue needs a multidimensional solution one of which is reduction of deadweight losses in university cost outlays.